2015
DOI: 10.3233/jcb-15003
|View full text |Cite
|
Sign up to set email alerts
|

Non-autologous endodontic pulp regeneration approach in molar teeth of the rat

Abstract: The dental pulp is an important soft connective tissue which is able to produce dentin over time as a reaction on external stimuli. It also maintains the biological and physiological vitality of the dentin. Due to this the pulp is essential for teeth homeostasis. However, dental caries is still one of the most prevalent health problems in dentistry and therefore, one major cause for early loss of the dental pulp vitality and subsequent tooth extractions. Meanwhile the potential for successful pulp regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…An extracted tooth germ is stored until use and the tooth grown from this germ by culture is transplanted into the defective portion of the tooth [26]. It was also reported that pulp was regenerated in a tooth root canal in which dental pulp had been lost [27] [28] [29]. However, considerable time is needed for tooth regeneration using induced pluripotent stem cells for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…An extracted tooth germ is stored until use and the tooth grown from this germ by culture is transplanted into the defective portion of the tooth [26]. It was also reported that pulp was regenerated in a tooth root canal in which dental pulp had been lost [27] [28] [29]. However, considerable time is needed for tooth regeneration using induced pluripotent stem cells for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models, especially rats, account for most animal investigations in pulp biology (5,6) . They are simple to handle and keep for extended periods, inexpensive, allow for larger sample numbers, are adapted to the lab setting, and have lower social and ethical problems than primates, making them excellent candidates (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The cell-based approach has utilized mice, rats, rabbits, ferrets, dogs, and miniswine to test pulp-dentin regeneration. 2,3,[8][9][10][11][12] The use of small animals has much to do with their ease of handling and economical nature. Nonetheless, large animals will eventually be needed to test conditions that highly mimic those in humans, especially considering work in the root canal space.…”
Section: Introductionmentioning
confidence: 99%